2022
DOI: 10.1039/d2ra03692d
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular hydrogen bonds between catechin and theanine in tea: slow release of the antioxidant capacity by a synergetic effect

Abstract: The health benefits of drinking tea stem from it being rich in polyphenols and other physiologically-active substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Many studies on the prevention and alleviation of obesity have been reported, some of which have focused on green tea ingredients. Tea catechin, a type of polyphenol contained in green tea, exerts an antioxidant effect [ 23 , 24 ]. Active oxygen causes aging of the human body, age spots, wrinkles, and lifestyle-related diseases, such as arteriosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on the prevention and alleviation of obesity have been reported, some of which have focused on green tea ingredients. Tea catechin, a type of polyphenol contained in green tea, exerts an antioxidant effect [ 23 , 24 ]. Active oxygen causes aging of the human body, age spots, wrinkles, and lifestyle-related diseases, such as arteriosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that L-theanine and caffeine bind with tea polyphenols and form complexes (Guo et al, 2021;Xia et al, 2022;Wang et al, 2023). The increase in L-theanine and caffeine levels during storage, as well as the increase in DPPH activity in spray-dried and freeze-dried tea samples, can be explained by the gradual release of these compounds from various complexes formed among them.…”
Section: Determination Of Moisture Content Of Powder Samples Prepared...mentioning
confidence: 99%